(untitled) (Papeles, 2022)
This paper analyzes, without any pretense of exhaustiveness, some flexibility mechanisms adopted in recent Latin American codifications that allow us to move away from rigid solutions, in the sector of international jurisdiction in order to serve the fair solution of private law cases with foreign elements in a concrete way.